Okra polysaccharide mitigates carrageenan-induced thrombosis in mice by regulating inflammation and oxidative stress - Ni, Jinping; Cao, Xiwen; Hu, Xianqing; Fu, Shenwen; Jiang, Meixiu; Ni, Yuqi (Frontiers in Pharmacology, 2025)
IntroductionThrombosis is a serious health hazard, which has been paid more and more attention.Okra polysaccharide (OP) is a biologically active substance extracted from okra which exhibits anti-inflammation and anti-oxidative properties. Nevertheless, the effect of OP on thrombosis is still unknown. In this study, we determined whether OP can suppress carrageenan-induced mice thrombosis and its involved mechanism.MethodsTwenty-four BALB/c mice were assigned to four groups randomly (6 mice/group): Ctrl, Model, OP low lose (OP-L, 200 mg/kg body weight), and OP high lose (OP-H,400 mg/kg body weight) were administered via intragastric administration for 9 days. Tails were photographed before collecting for H&E and Masson staining. Liver and lung tissues were collected for H&E staining, RT-qPCR, Western blot and GSH content detection. Injury or dysfunction of endothelial cells (ECs) was assessed using RT-qPCR, Western blot and cell adhesion assays.ResultsOP can effectively improve carrageenan-induced thrombosis in tissues of mice (tail, liver, and lung) in vivo. In addition, OP inhibited inflammation by suppressing the toll-like receptor 4 (TLR4)/nuclear factor κB (NF-κB) pathway and reduced oxidative damage by elevating the level of GSH and antioxidant enzyme in liver and lung tissues. In vitro, OP inhibited thrombin-induced human platelet clots retraction, and decreased lipopolysaccharide (LPS)-activated adhesion of THP-1 monocytes to human umbilical vein endothelial cells(HUVECs) by suppressing intercellular adhesion molecule-1 (ICAM-1) level.DiscussionIn conclusion, OP can inhibit thrombosis in mouse model by regulating inflammation and oxidative stress, which suggest that OP could act as a potential functional food for prevention of thrombus.